Retinal nerve fiber layer defects and chronic kidney disease: the Kailuan Eye Study - Wan, Qian-Qian; Fang, Li-Jian; Wang, Ya-Xing; Wang, Ye-Nan; Wang, Qian; Yan, Yan-Ni; Yang, Xuan; Wu, Shou-Ling; Chen, Shuo-Hua; Jonas, Jost B; Wei, Wen-Bin (International journal of ophthalmology, 2024)
AIM: To investigate whether retinal nerve fiber layer defects (RNFLDs) is a potential risk factor for chronic kidney disease (CKD) in Chinese adults. METHODS: The Kailuan Eye Study was a population-based study that included 14 440 participants. All participants underwent detailed assessments, RNFLDs were diagnosed using color fundus photographs. RESULTS: Overall, 12 507 participants [8533 males (68.23%)] had complete systemic examination data and at least one evaluable fundus photograph. RNFLDs were found in 621 participants [5.0%; 95% confidence interval (CI): 4.6%-5.34%], and 70 cases of multiple RNFLDs were found (11.27%). After adjusting multiple factors, RNFLDs was significantly associated with CKD severity, the ORs of CKD stage 3, stage 4 and stage 5 were 1.698, 4.167, and 9.512, respectively. Multiple RNFLDs were also associated with CKD severity after adjusting multiple factors, the ORs of CKD stage 3 and stage 5 were 4.465 and 11.833 respectively. Furthermore, 2294 participants had CKD (18.34%, 95%CI: 17.68%-18.99%). After adjusting for other factors, CKD presence was significantly correlated with the presence of RNFLDs. CONCLUSION: The strongest risk factors for RNFLDs are CKD and hypertension. Conversely, RNFLDs can be an ocular feature in patients with CKD. Fundoscopy can help detect systemic diseases, and assessment for RNFLDs should be considered in CKD patients.